Research in geography - Singh, R. B. (Ram Babu), 1955- (New Delhi : A.P.H. Pub. Corp., 1996)
Papers presented at a seminar held at University of Delhi in Dec. 1991.
v. 1. Land use changes and sustainable development -- v. 2. Disasters and environment, monitoring and forecasting.
Includes bibliographical references and index.
Keywords: Geography -- Congresses